Answer:
See below.
Step-by-step explanation:
4)
So we have the expression:
![(-6n^{-3})^2](https://tex.z-dn.net/?f=%28-6n%5E%7B-3%7D%29%5E2)
We can use the power of a product property, where:
![(ab)^n=a^n\cdot b^n](https://tex.z-dn.net/?f=%28ab%29%5En%3Da%5En%5Ccdot%20b%5En)
So:
![=(-6)^2\cdot(n^{-3})^2](https://tex.z-dn.net/?f=%3D%28-6%29%5E2%5Ccdot%28n%5E%7B-3%7D%29%5E2)
For the left, -6 squared is the same as -6 times -6. This equals positive 36.
For the right, we can use the power of a power property. The property says that:
![(a^n)^k=a^{nk}](https://tex.z-dn.net/?f=%28a%5En%29%5Ek%3Da%5E%7Bnk%7D)
So:
![(n^{-3})^2=n^{(-3)(2)}\\=n^{-6}](https://tex.z-dn.net/?f=%28n%5E%7B-3%7D%29%5E2%3Dn%5E%7B%28-3%29%282%29%7D%5C%5C%3Dn%5E%7B-6%7D)
So, all together, we have:
![=(-6)^2\cdot(n^{-3})^2\\=36n^{-6}](https://tex.z-dn.net/?f=%3D%28-6%29%5E2%5Ccdot%28n%5E%7B-3%7D%29%5E2%5C%5C%3D36n%5E%7B-6%7D)
6)
We have the expression:
![-\frac{3x^0}{x^4}](https://tex.z-dn.net/?f=-%5Cfrac%7B3x%5E0%7D%7Bx%5E4%7D)
First, note that anything to the zeroth power (except for 0) is 1, thus, x^0 is also 1. Simplify:
![=-\frac{3}{x^4}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B3%7D%7Bx%5E4%7D)
And that's the simplest we can do :)
Notes for 6)
We <em>can</em> put the x^4 to the numerator. Recall that when you put an exponent to opposite side, you put a negative. In other words:
![x^n=\frac{1}{x^{-n}}](https://tex.z-dn.net/?f=x%5En%3D%5Cfrac%7B1%7D%7Bx%5E%7B-n%7D%7D)
And vice versa:
![\frac{1}{x^{-n}}=x^n](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%5E%7B-n%7D%7D%3Dx%5En)
So, we can write the above as:
![=-\frac{3}{x^4}\\=-\frac{3}{x^{-(-4)}}\\=-3x^{-4}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B3%7D%7Bx%5E4%7D%5C%5C%3D-%5Cfrac%7B3%7D%7Bx%5E%7B-%28-4%29%7D%7D%5C%5C%3D-3x%5E%7B-4%7D)
However, traditionally, we want only positive exponents, so this wouldn't be correct.